Did Russia’s Soft Power Really Work? An Initial Survey of Russia’s Soft Power Attraction in Indonesia - Archellie , Reynaldo de’; Arumsari, Chysanti (Southeast Asia Development Research, 2025)
Russia has been trying to change its image in global politics since the demise of the Soviet Union. One of the most popular tools the Russian government used to do this is soft power resources. The exploration of Russia’s soft power can be seen from the Concept of the Foreign Policy of the Russian Federation in 2016, which places more emphasis on the use of soft power instruments in the implementation of foreign policy. This article attempts to explore and understand the type and use of soft power resources of Russia in Indonesia. By using a constructive perspective and descriptive statistical methods, this article will capture how the Indonesian young generation perceives the type and the use of Russia’s soft power resources in Indonesia. However, this study’s data, collected in 2018, precedes the signifcant geopolitical shifts following Russia’s 2022 military actions in Ukraine, which may have altered global perceptions. Our results showed that Russian soft power resources emanated from Russian culture and Cold War historical remnants have been successfully converted into soft power attractions for foreign audiences in Indonesia. It indicates a shared understanding of the respondents about global multipolarity in which Russia was perceived as a balancing great power of US domina-tion.